1992
DOI: 10.1021/jm00085a004
|View full text |Cite
|
Sign up to set email alerts
|

Development of a series of phenyltetrazole leukotriene D4(LTD4) receptor antagonists

Abstract: A hypothetical model for receptor binding of leukotriene D4 (LTD4) was deduced from conformational analysis of LTD4 and from the structure-activity relationships (SAR) of known LTD4 receptor antagonists. A new structural series of LTD4 receptor antagonists exemplified by 5-[4-(4-phenylbutoxy)phenyl]-2-[4-(tetrazol-5-yl)butyl]-2H-t etrazole was designed in which a phenyltetrazole moiety was incorporated as a receptor binding equivalent of the triene unit of LTD4. A number of these phenyltetrazoles were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…HGF may mediate mitogenic action on the ovarian surface epithelium after ovulation. Early studies examining the action of HGF on ovarian surface epithelial cell proliferation have reported conflicting results [ 44 , 45 ]. This study showed that the ovarian surface epithelium expresses the HGF receptor MET, which responds to HGF in FF/PF with autophosphorylation and induces cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…HGF may mediate mitogenic action on the ovarian surface epithelium after ovulation. Early studies examining the action of HGF on ovarian surface epithelial cell proliferation have reported conflicting results [ 44 , 45 ]. This study showed that the ovarian surface epithelium expresses the HGF receptor MET, which responds to HGF in FF/PF with autophosphorylation and induces cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…HGF may mediate mitogenic action on the OSE after ovulation. Early studies examining the action of HGF on OSE cell proliferation have reported conflicting results (Gubbay et al, 2004;Harper et al, 1992). This study showed that the OSE expresses the HGF receptor c-MET, which responds to HGF in FF/PF with autophosphorylation and induces cell proliferation.…”
Section: Physiological Rolementioning
confidence: 91%
“…The hydroxyacetophenone pharmacophore of this compound became an important component in a series number of potential LT receptor antagonists [22,[66][67][68].…”
Section: Leukotriene Receptor Antagonistsmentioning
confidence: 99%